Physiological and anatomical changes in a woman’s body during pregnancy - Serdan Ruiz, David Leonardo; Vasquez Bone, Katterine Kariuxy; Yupa Pallchisaca, Ana Emperatriz (Universidad Ciencia y Tecnología, 2023)
The woman’s body suffers important transformations during pregnancy, among which the hormonal changes characteristic of her state and the placental process can be mentioned. These processes will culminate with the birth of the baby. At this stage, the OB/GYN represents a figure of great importance, which is responsible for supervising and ensuring that all natural processes follow a normal course and that the health of the mother and fetus can be the most suitable until the end the gestation process. In this work, a bibliographic review is made to know the processes of change in the pregnant woman, the care that should be followed, and the possible associated risks.